PEMANFAATAN LIMBAH DAPUR MENJADI PUPUK ORGANIK CAIR (POC) UNTUK DILINGKUNGAN MASYARAKAT RW 03 KELURAHAN JEMBATAN KECIL - Pebrian Miqdat (UNIB Press, 2025)
Organic fertilizer is a type of fertilizer derived from natural materials such as plant and animal residues that have undergone specific processing. One form of this is Liquid Organic Fertilizer (LOF), which is typically made from vegetable waste and is easy to produce. The production process of LOF is carried out naturally through fermentation, during which plant residues and animal waste decompose. The main goal of producing LOF is to convert kitchen or household waste into a useful product. This process also aims to identify the most effective method for producing liquid fertilizer by utilizing household organic waste as the main material, enhanced with the addition of EM4 (Effective Microorganisms 4).